2012
DOI: 10.1097/nmd.0b013e3182532062
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Investigation of Depressive Symptoms in Undergraduate Students of Pharmacy in Syria

Abstract: This prospective longitudinal study investigated depressive symptoms and its association with students' demographic, academic, and health factors in undergraduate students of pharmacy in Syria. Students attending any year (1st to 5th year) were assessed in the first semester (time 1) and in the second semester (time 2). An academic year comprises two semesters of 16 weeks each. Data for 450 students were analyzed at time 1, and 262 students were assessed at the two time points. Our results showed that most of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 27 publications
1
13
0
9
Order By: Relevance
“…This relation between mental health problems and academic performance was also verified in other comparative studies on different mental health problems (Castaño-Perez & Calderon-Vallejo, 2014;Gonçalves et. al., 2012;Hernández-Pozo et al, 2008).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…This relation between mental health problems and academic performance was also verified in other comparative studies on different mental health problems (Castaño-Perez & Calderon-Vallejo, 2014;Gonçalves et. al., 2012;Hernández-Pozo et al, 2008).…”
Section: Discussionmentioning
confidence: 61%
“…In this scenario, other variables have been considered relevant to understand the academic performance, such as social skills (Aguilar, 2008;Artino et al, 2012;Fernandez, Salamonson, & Griffiths, 2012;Gomes & Soares, 2013;Ihm, Lee, Kim, Jang, & Jin, 2013;Oyarzún Iturra, Estrada Goic, Pino Astete, & Oyarzún Jara, 2012;Victoroff & Boyatzis, 2013); mental health conditions, such as anxiety (Costales & Neira, 2011;Hernández-Pozo, Coronado Álvarez, Araújo Contreras, & Cerezo Reséndiz, 2008), depression (Gonçalves, Zidan, Issa, & Barah, 2012;Turner, Thompson, Huber, & Arif, 2012) and drugs use (Bajwa et al, 2013;Castaño-Perez & Calderon-Vallejo, 2014); besides academic variables like knowledge areas (Garzella, 2013) and courses (Martí Ballester, 2012).…”
mentioning
confidence: 99%
“…The relationship between academic performance and school anxiety was approached by Hernández-Pozo et al (2008), with Mexican students, with it being found that those who had academic difficulties presented increased rates of depression, anxiety, suicidal ideation, and impoverished interpersonal relationships. Similarly, with Syrian university, Gonçalves et al (2012) found that the lower the academic performance at the end of the course, the higher the depression scores at the beginning of the course, and at the end of the course, with these scores increasing with decreasing expectations of academic performance. The authors emphasized that poor school performance can act as a factor that contributes to the development of depressive symptoms.…”
mentioning
confidence: 81%
“…The associations can be bidirectional with respect to academic performance and mental health, with deficient academic performance negatively influencing mental health (Hernández-Pozo, Àlvarez, Contreras & Reséndiz, 2008;López-Bárcena, González-de Cossío, Ávila-Martínez & Teos-Aguilar., 2009), or with mental health problems interfering with academic performance (Gonçalves et al, 2012;Turner, Thompson, Huber & Arif, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation